Study protocol for the POPART study—Prophylactic Oropharyngeal surfactant for Preterm infants: A Randomised Trial - Murphy, Madeleine Claire (BMJ Open, 2020)
INTRODUCTION: Many preterm infants develop respiratory distress syndrome (RDS), a condition characterised by a relative lack of surfactant. Endotracheal surfactant therapy revolutionised the care of preterm infants in the 1990s. However, supporting newborns with RDS with continuous positive airway pressure (CPAP) and reserving endotracheal surfactant for those who develop respiratory failure despite CPAP yield better results than intubating all infants for surfactant. Half of preterm infants born before 29 weeks gestation initially managed with CPAP are intubated for surfactant. Intubation is difficult to learn and associated with adverse effects. Surfactant administration into the oropharynx has been reported in preterm animals and humans and may be effective. We wished to determine whether giving oropharyngeal surfactant at birth reduces the rate of endotracheal intubation for respiratory failure in preterm infants within 120 hours of birth. METHODS AND ANALYSIS: Prophylactic Oropharyngeal surfactant for Preterm infants: A Randomised Trial (POPART, Eudract No. 2016-004198-41) is an investigator-led, unblinded, multicentre, randomised, parallel group, controlled trial. Infants are eligible if born at a participating centre before 29 weeks gestational age (GA) and there is a plan to offer intensive care. Infants are excluded if they have major congenital anomalies. Infants are randomised at birth to treatment with oropharyngeal surfactant (120 mg vial <26 weeks GA stratum; 240 mg vial 26–28(+6) weeks GA stratum) in addition to CPAP or CPAP alone. The primary outcome is intubation within 120 hours of birth, for bradycardia and/or apnoea despite respiratory support in the delivery room or respiratory failure in the intensive care unit. Secondary outcomes include incidence of mechanical ventilation, endotracheal surfactant use, chronic lung disease and death before hospital discharge. ETHICS AND DISSEMINATION: Approval for the study has been granted by the Research Ethics Committees at the National Maternity Hospital, Dublin, Ireland (EC31.2016) and at each participating site. The trial is being conducted at nine centres in six European countries. The study results will be submitted for publication in a peer-reviewed journal. TRIAL REGISTRATION NUMBER: 2016-004198-41; Pre-results.